HDncRNA: a comprehensive database of non-coding RNAs associated with heart diseases. (24th July 2018) - Wang, Wen-Jing; Wang, Yu-Mei; Hu, Yi; Lin, Qin; Chen, Rou; Liu, Huan; Cao, Wen-Ze; Zhu, Hui-Fang; Tong, Chang; Li, Li; Peng, Lu-Ying
Abstract: Heart diseases (HDs) represent a common group of diseases that involve the heart, a number of which are characterized by high morbidity and lethality. Recently, increasing evidence demonstrates diverse non-coding RNAs (ncRNAs) play critical roles in HDs. However, currently there lacks a systematic investigation of the association between HDs and ncRNAs. Here, we developed a Heart Disease-related Non-coding RNAs Database (HDncRNA), to curate the HDs-ncRNA associations from 3 different sources including 1904 published articles, 3 existing databases [the Human microRNA Disease Database (HMDD), miR2disease and lncRNAdisease] and 5 RNA-seq datasets. The HDs-ncRNA associations with experimental validations curated from these articles, HMDD, miR2disease and part of data from lncRNAdisease were 'direct evidence'. Relationships got from high-through data in lncRNAdisease and annotated differential expressed lncRNAs from RNA-seq data were defined as 'high-throughput associations'. Novel lncRNAs identified from RNA-seq data in HDs had least credibility and were defined as 'predicted associations'. Currently, the database contains 2304 HDs-ncRNA associations for 133 HDs in 6 species including human, mouse, rat, pig, calf and dog. The database also has the following features: (i) A user-friendly web interface for browsing and searching the data; (ii) a visualization tool to plot miRNA and lncRNA locations in the human and mouse genomes; (iii) information about neighboring genes of lncRNAs and (iv) links to some mainstream databases including miRbase, Ensemble and Fantom Cat for the annotated lncRNAs and miRNAs. In summary, HDncRNA provides an excellent platform for exploring HDs related ncRNAs. Database URL: http://hdncrna.cardiacdev.com